Association of the Leukocyte Immunoglobulin‐like Receptor A3 Gene With Neutrophil Activation and Disease Susceptibility in Adult‐Onset Still's Disease. Issue 6 (2nd May 2021) - Wang, Mengyan; Liu, Mengru; Jia, Jinchao; Shi, Hui; Teng, Jialin; Liu, Honglei; Sun, Yue; Cheng, Xiaobing; Ye, Junna; Su, Yutong; Chi, Huihui; Liu, Tingting; et al.
Abstract : Objective: Adult‐onset Still's disease (AOSD) is a severe autoinflammatory disease. Neutrophil activation with enhanced neutrophil extracellular trap (NET) formation is involved in the pathogenesis of AOSD. Functional leukocyte immunoglobulin‐like receptor A3 (LIR‐A3; gene name LILRA3 ) has been reported to be associated with many autoimmune diseases. We aimed to investigate the association of LILRA3 with disease susceptibility and neutrophil activation in AOSD. Methods: The LILRA3 deletion polymorphism and its tagging single‐nucleotide polymorphism rs103294 were genotyped in 164 patients with AOSD and 305 healthy controls. The impact of LILRA3 on clinical features and messenger RNA expression was evaluated. Plasma levels of LIR‐A3 were detected using enzyme‐linked immunosorbent assay (ELISA), and the correlation between LIR‐A3 plasma levels and disease activity and levels of circulating NET‐DNA was investigated. LIR‐A3–induced NETs were determined using PicoGreen double‐stranded DNA dye and immunofluorescence analysis in human neutrophils and a neutrophil‐like differentiated NB4 cell line transfected with LIR‐B2 small interfering RNA. Results: The findings from genotyping demonstrated that functional LILRA3 was a risk factor for AOSD (11% in AOSD patients versus 5.6% in healthy controls; odds ratio 2.089 [95% confidence interval 1.030–4.291], P  = 0.034), and associated with leukocytosis ( P = 0.039) and increased levels of circulating neutrophils ( P = 0.027). Functional LILRA3 messenger RNA expression was higher in the peripheral blood mononuclear cells ( P < 0.0001) and neutrophils ( P < 0.001) of LILRA3 +/+ patients. Plasma levels of LIR‐A3 were elevated in patients with AOSD ( P < 0.0001) and correlated with disease activity indicators and levels of circulating NET–DNA complexes. Finally, enhanced NET formation was identified in neutrophils from healthy controls and patients with inactive AOSD after stimulation of the neutrophils with LIR‐A3. Moreover, NET formation was impaired in NB4 cells after knockdown of LILRB2 gene expression. Conclusion: Our study provides the first evidence that functional LILRA3 is a novel genetic risk factor for the development of AOSD and that functional LIR‐A3 may play a pathogenic role by inducing formation of NETs.